2020
DOI: 10.3390/life10070111
|View full text |Cite
|
Sign up to set email alerts
|

Embelin as Lead Compound for New Neuroserpin Polymerization Inhibitors

Abstract: Familial encephalopathy with neuroserpin inclusion bodies (FENIB) is a severe and lethal neurodegenerative disease. Upon specific point mutations in the SERPINI1gene-coding for the human protein neuroserpin (NS) the resulting pathologic NS variants polymerize and accumulate within the endoplasmic reticulum of neurons in the central nervous system. To date, embelin (EMB) is the only known inhibitor of NS polymerization in vitro. This molecule is capable of preventing NS polymerization and dissolving preformed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Catalytic (10 %) amounts of manganese acetate dihydrate (MAH) could efficiently promote the addition of n ‐butylamine to CBDQ ( 1 a ) without replacing the enolic hydroxyl with an amine functionality, a known reaction of O ‐alkyl hydroxyquinones, or generating iminoquinones (Scheme 2). [9] MAH could efficiently promote the addition of various primary amines to both CBDQ ( 1 a ) and CBGQ ( 2 a ). Conversely, secondary amines were unreactive, presumably for steric reasons associated to the presence of the adjacent n ‐pentyl group on the quinone core.…”
Section: Resultsmentioning
confidence: 99%
“…Catalytic (10 %) amounts of manganese acetate dihydrate (MAH) could efficiently promote the addition of n ‐butylamine to CBDQ ( 1 a ) without replacing the enolic hydroxyl with an amine functionality, a known reaction of O ‐alkyl hydroxyquinones, or generating iminoquinones (Scheme 2). [9] MAH could efficiently promote the addition of various primary amines to both CBDQ ( 1 a ) and CBGQ ( 2 a ). Conversely, secondary amines were unreactive, presumably for steric reasons associated to the presence of the adjacent n ‐pentyl group on the quinone core.…”
Section: Resultsmentioning
confidence: 99%
“…Embelin, a small molecule derived from the Japanese Ardisia herb, prevented in vitro NS aggregation and dissolve aggregates. 67,68 ABE correction of the pathogenic variant to prevent new aggregation combined with embelin disruption of existing aggregates is a potential effective therapy.…”
Section: Discussionmentioning
confidence: 99%
“…2 B, oligomers NS-EMB ) [ 53 ]. Unfortunately, several attempts to ameliorate the solubility of embelin and its affinity for neuroserpin have shown that even minor chemical modifications result in a marked reduction of its antipolymerisation activity [ 65 ].…”
Section: Polymerisation Of Neuroserpinmentioning
confidence: 99%